THE IMPORTANCE OF INCLUSIVE EDUCATION FOR A DIVERSE SOCIETY - Nilna Mayang Kencana Sirait; Sondang Siregar; Sari Harahap (International Journal of Teaching and Learning, 2025)
This study aims to analyze the importance of inclusive education in improving the quality and harmony of a diverse society. This literature review covers various academic sources that explore the concept, implementation, and impact of inclusive education on students with different backgrounds and society as a whole. Specifically, this study examines how inclusive education can improve accessibility and equality of learning opportunities for all students, reduce stigma and discrimination against individuals with special needs, and promote tolerance, empathy, and adaptability in a pluralistic society. The results of the literature show that the implementation of inclusive education has a positive contribution in creating a fair and supportive learning environment for all learners. Inclusive education is not only beneficial for students with special needs, but also for majority students who learn to appreciate diversity and strengthen their social skills. In addition, the findings of the literature confirm that inclusive education is an important step towards developing an inclusive, egalitarian, and cooperative society, where every individual has an equal opportunity to develop their potential and contribute to community development. Thus, this study underlines the urgency of implementing inclusive education as a primary strategy in preparing the younger generation to face and appreciate diversity, as well as fostering a more just and harmonious society.